2009
DOI: 10.1080/15265160802617829
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Challenges and Interpretive Difficulties with Non-Clinical Applications of Pediatric fMRI

Abstract: In this article, we critically examine some of the ethical challenges and interpretive difficulties with possible future non-clinical applications of pediatric fMRI with a particular focus on applications in the classroom and the courtroom - two domains in which children come directly in contact with the state. We begin with a general overview of anticipated clinical and non-clinical applications of pediatric fMRI. This is followed by a detailed analysis of a range of ethical challenges and interpretive diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Though the reality is much more problematic than its popular representation (cf. Fenton et al [19,20]), as Rose claims, "most accounts that make use of these technologies write as if we can now visualize the interior of the living human brain and observe its activity in real time as it thinks, perceives, emotes, and desires-we can see 'mind' in the activities of the living brain" [18:196]. It has been reported that a group of neuroscientists at the Max Planck Institute for Human Cognitive and Brain Sciences have, for instance, recently announced a technique using high-resolution brain scans which they claim makes possible the ability to look "inside" a subject's brain so as to read the person's intentions [21].…”
Section: Novel Neurotechnologies "Pre-figured" In Minority Reportmentioning
confidence: 98%
“…Though the reality is much more problematic than its popular representation (cf. Fenton et al [19,20]), as Rose claims, "most accounts that make use of these technologies write as if we can now visualize the interior of the living human brain and observe its activity in real time as it thinks, perceives, emotes, and desires-we can see 'mind' in the activities of the living brain" [18:196]. It has been reported that a group of neuroscientists at the Max Planck Institute for Human Cognitive and Brain Sciences have, for instance, recently announced a technique using high-resolution brain scans which they claim makes possible the ability to look "inside" a subject's brain so as to read the person's intentions [21].…”
Section: Novel Neurotechnologies "Pre-figured" In Minority Reportmentioning
confidence: 98%
“…Apart from the obvious clinical interest in pediatric fMRI, like the support of brain surgery or the diagnosis of conditions and diseases, the technique of fMRI has a great potential for developing non-clinical applications, for example in the field of jurisprudence (e.g., lie detection, moral decision making, accountability), education (e.g., memory enhancement), or marketing (e.g., consumer brand attachment, persuasion), several of which have been registered already [18].…”
Section: Non-clinical Research Objectivesmentioning
confidence: 99%
“…Such an introduction of new sponsors generates specific ethical and regulatory issues, as new players in the field may lack familiarity with clinical research and expertise in dealing with research subjects in an ethical way [18].…”
Section: Non-clinical Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, an investigator could present a suspect with specific information such as of passwords, social security numbers, credit card information, other personal information, or other confidential corporate information [35]. This scientific technique allows intelligence operatives to focus their investigations on the suspects who actually commit crime and to determine if he or she has any un-authorized access to an organization's network or system before (See [22] [25] [26] [29] [33] [35]). On the other side, an information absent will provide support for the claims of innocence that employee is not guilty of committing any crime and has no knowledge specific to any data or any information [37].…”
Section: Maintaining Security Using Functionalmentioning
confidence: 99%